Preserving Indigenous Knowledge Through Lis: Exploring the Role of Information Management in Preserving Indigenous Knowledge (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper discusses the characteristics andsignificance of indigenous knowledge; reviews the process of capturing and preservingIK; analyses the existing information management literature on IK; examines therole of  information  management in  IK  in light  of  reported experience, especially in Africa and Australia; proposes thatinformation management discipline review its curricula to accommodate areasneeded, and work for the development of tools and techniques for IK management